T Model riset transformatif–partisipatoris dalam Pendidikan Agama Islam: Studi aplikatif di pesantren, madrasah, dan PTKI - Hayat, Ade Putra; Sesmiarni, Zulfani (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
This study aims to examine the implementation of the transformative–participatory research (TPR) model in Islamic Religious Education (PAI) across three institutional contexts: pesantren (Islamic boarding schools), madrasah, and Islamic Higher Education Institutions (PTKI). The research is grounded in the awareness that conventional methodological approaches in Islamic education research often remain normative and descriptive, failing to address the complex social, cultural, and spiritual realities of Muslim communities. Using a qualitative approach through conceptual and critical literature analysis, this study explores the philosophical and epistemological foundations of the TPR model, which emphasizes social transformation, tawhīdic consciousness, and community participation in educational processes. The findings reveal that the application of TPR in pesantren revitalizes the traditional talaqqī method into a dialogical and collaborative praxis; in madrasah, it shifts pedagogy from a teacher-centered to a student- and community-centeredparadigm; while in PTKI, it fosters a reflective and socially engaged research culture. Theoretically, the TPR model enriches the epistemology of Islamic education by integrating faith, knowledge, and action; practically, it strengthens Islamic education as a medium of empowerment and civilizational development. Therefore, transformative–participatory research can be viewed as a new paradigm reaffirming the Islamic scientific identity amid the dynamics of modernity and global social challenges. Abstrak Penelitian ini bertujuan untuk mengkaji implementasi model riset transformatif–partisipatoris (RTP) dalam Pendidikan Agama Islam (PAI) pada tiga konteks kelembagaan: pesantren, madrasah, dan Perguruan Tinggi Keagamaan Islam (PTKI). Kajian ini berangkat dari kesadaran bahwa pendekatan metodologis konvensional dalam riset PAI sering kali bersifat normatif dan deskriptif, sehingga kurang mampu menjawab persoalan sosial, kultural, dan spiritual umat. Melalui pendekatan kualitatif dengan analisis konseptual dan studi pustaka kritis, penelitian ini menguraikan landasan filosofis dan epistemologis model RTP yang berorientasi pada transformasi sosial, kesadaran tauhidik, dan partisipasi komunitas pendidikan. Hasil kajian menunjukkan bahwa penerapan model RTP di pesantren mendorong reaktualisasi tradisi talaqqī menjadi praksis dialogis dan kolaboratif; di madrasah, model ini menggeser paradigma pedagogi dari teacher-centered menuju student-community-centered; sedangkan di PTKI, pendekatan ini membentuk budaya riset reflektif dan kolaboratif berbasis pengabdian sosial. Secara teoretis, model RTP memperkaya epistemologi riset Pendidikan Islam dengan menegaskan integrasi antara iman, ilmu, dan amal; secara praktis, ia memperkuat peran pendidikan Islam sebagai instrumen pemberdayaan umat dan pembangunan peradaban. Oleh karena itu, riset transformatif–partisipatoris dapat dipandang sebagai paradigma baru yang meneguhkan identitas keilmuan Islam di tengah dinamika modernitas dan tantangan sosial global.